Consumer Innovation at the Base of the Pyramid Emerging Patterns of User Innovation in a Resource-Scarce Setting - Praceus, Sarah. (Forschungs-/Entwicklungs-/Innovations-Management, 2014)
Approximately one-third of the world’s population lives in poverty at the global Base of the economic Pyramid (BoP). Sarah Praceus quantitatively investigates patterns and characteristics of a large sample of innovations developed by people living at the BoP in India. Their differences and commonalities versus consumer innovations from the developed world are identified. Furthermore, Sarah Praceus examines the effects of innovation-relevant resources and contextual factors on the innovative outcomes at the BoP. The findings indicate that poor consumer innovators and their wealthier counterparts share similar stable demographic predispositions and preferences while the phenomenon adapts to the different living conditions at the BoP. Finally, user innovation research from developed markets appears not to be entirely transferable to subsistence markets.   Contents n  Base of the Pyramid (BoP) n  User Innovation n  Patterns and Antecedents of Consumer Innovation at the BoP   Target Groups ·        Researchers and students in the field of innovation management, user innovation and BoP ·        Entrepreneurs and organizations striving for new business opportunities in subsistence markets and practitioners interested in product development for the BoP   The Author Sarah Praceus obtained her doctorate at the Institute for Technology and Innovation Management at the Hamburg University of Technology (TUHH).